Investigation of spectral properties of different Quaternary paleosols and parent materials - József Szeberényi; Alzbeta Medved’ová; Pavel Rostinsky; Gabriella Barta; Ágnes Novothny; Diána Csonka; István Viczián; Erzsébet Horváth; Tamás Végh (Hungarian Geographical Bulletin, 2020)
Diffuse Reflectance Spectroscopy (DRS) is a rapid, relatively new method in Quaternary research to analyse sediments and paleosols. This method takes into account clay mineral content, amount of Fe-bearing minerals and grain size composition of samples, simultaneously. Different Quaternary sediment samples were chosen forcharacterization and comparison their reflectance curves to detect the essential spectral properties of differentpaleosols and parent materials. Samples of different sediment types and paleosol variants were investigatedfrom a loess-paleosol sequence from Malá nad Hronom (Slovakia) and from a fluvial-aeolian sediment complex from Pilismarót (Hungary). Five investigated curve sections were separated as the best indicators of reflectance properties of DRS curves. Spectral properties of samples were compared by using the length of investigated curve sections. This investigation showed quantifiable differences between the units of Pleistocene sediment successions, based on the reflectance properties. The influence of pedogenic processes was properly detectable. Significant discrepancies were observed between reflectance curves of well-developed paleosols and parent material samples in the visible and near-infrared range. Differences between the weak developed paleosol layers and their parent materials were only observed in the visible range. Fine sand, sandy silt and loess materials could be separated from each other based on the intensity of entire reflectance curves.